Intermediate monocytes but not TIE2-expressing monocytes are a sensitive diagnostic indicator for colorectal cancer. - Dominic Schauer; Patrick Starlinger; Christian Reiter; Nikolaus Jahn; Philipp Zajc; Elisabeth Buchberger; Thomas Bachleitner-Hofmann; Michael Bergmann; Anton Stift; Thomas Gruenberger; Christine Brostjan (PLoS ONE, 2012)
We have conducted the first study to determine the diagnostic potential of the CD14++CD16+ intermediate monocytes as compared to the pro-angiogenic subset of CD14++CD16+TIE2+ TIE2-expressing monocytes (TEMs) in cancer. These monocyte populations were investigated by flow cytometry in healthy volunteers (N = 32) and in colorectal carcinoma patients with localized (N = 24) or metastatic (N = 37) disease. We further determined blood levels of cytokines associated with monocyte regulation. The results revealed the intermediate monocyte subset to be significantly elevated in colorectal cancer patients and to show the highest frequencies in localized disease. Multivariate regression analysis identified intermediate monocytes as a significant independent variable in cancer prediction. With a cut-off value at 0.37% (intermediate monocytes of total leukocytes) the diagnostic sensitivity and specificity ranged at 69% and 81%, respectively. In contrast, TEM levels were elevated in localized cancer but did not differ significantly between groups and none of the cytokines correlated with monocyte subpopulations. Of interest, in vitro analyses supported the observation that intermediate monocytes were more potently induced by primary as opposed to metastatic cancer cells which may relate to the immunosuppressive milieu established in the advanced stage of metastatic disease. In conclusion, intermediate monocytes as compared to TIE2-expressing monocytes are a more sensitive diagnostic indicator of colorectal cancer.